US Food Shopper Trends in 2017 - Lijun Angelia Chen; Lisa House (EDIS)
This study provides an overview of US food shoppers in 2017 and serves as a benchmark for analyzing consumer trends in the future. A nationwide sample of 5,993 adults, primary food shoppers in the United States completed a survey in 2017 to learn about food-related perspectives and trends. Consumers differ in food shopping outlets, grocery spending, response to food price increases, food-related attitudes, food and beverage consumption patterns, and nutritional perceptions.